Avaliação da adaptação de bovinos da raça nelore ao ambiente tropical - Storti, Andressa Alves (2020)
The first study aimed to determine among 16 thermal indexes, which are more suitable to identify the effects of heat stress in Nellore bulls bred in a tropical environment. 78 young Nellore bulls (Bos taurus indicus) were used, participating in the V Individual Performance Test of Nellore Bulls, UFU. During the test, the rectal temperature (RT) and the surface temperature on the forehead, scapula and groin were measured in the animals, and then the average surface temperature (AST) was calculated. It was also calculated the difference between the average surface temperature and the air temperature (AST-AT) and the difference between the rectal temperature and the average surface temperature (RT-AST), constituting the thermal gradients. In the thermal environment, dry bulb, wet bulb and black globe temperatures, wind speed, relative humidity and partial vapor pressure were evaluated. Then the average radiant temperature, solar radiation and the Black Globe and Humidity Index (BGHI), Equivalent Temperature Index (ETI), Environmental Stress Index (ESI), Respiratory Rate Predictor (PRR), Thermal Load Index (TLI), Comprehensive Climate Index (CCI), Index Thermal Stress for cows (ITSC) and nine Temperature and Humidity Indexes (THI). The sixteen heat stress indices showed a significant, positive and moderate correlation with the average surface temperature, and not significant with the rectal temperature. When considering that there was no correlation between the thermal stress indexes and the rectal temperature, and even considering that the cattle were able to maintain their rectal temperature within the physiological limits, the Nellore bulls in this study proved to be adapted to the environment. The second study verified the effect of thermophysiological variables at the time of artificial insemination on the pregnancy probability of Nellore bovine females. A total of 816 inseminations of Nellore bovine females were followed, submitted to a fixed-time artificial insemination protocol (FTAI), for five years. At the time of artificial insemination, respiratory rate, rectal and surface temperatures, as well as dry bulb, wet bulb, globe temperature and wind speed temperatures were measured. The Temperature-Humidity Index (THI), Equivalent Temperature Index (ETI), Thermal Load Index (TLI) and solar radiation were calculated. The surface temperature was measured in the forehead (TF) and scapula (TS), obtaining the mean body surface temperature (STM). The difference between the temperature of the mean surface temperature and dry bulb (STM-TDB) and the difference between rectal temperature and the mean surface temperature (RT–STM) was also calculated, constituting the thermal gradients. The pregnancy diagnosis was made on the 28th day after insemination. The number of pregnant or non-pregnant bovine females did not differ between the groups of rectal temperature (RT ≤ 38.7) and (RT> 38.7 ºC). TF and TS showed a significant, positive and high correlation with STM. Factor 1 explained 51.05% of the data variation and the variables with the greatest influence on the composition of this factor are THIBerman, THIThom, TDB, STM, TG, ETI, TF, TLI, PV and TS. TF and STM showed significant, positive and moderate correlations with TDB, PV, TG, THI, TLI and ETI. The probability of pregnancy was not influenced when the animals were divided into groups by the rectal temperature (RT ≤38.7 ºC and RT> 38.7 ºC). In the Cerrado biome, the rectal temperature and the thermal environment in spring and summer, at the time of insemination of Nellore bovine females submitted to FTAI protocol do not influence the probability of pregnancy.